Strength and Interface Adhesion Properties of in-Plane Shear Loaded Thick Adhesive Joint - Muhamad Azlan, Hafizah; Francis, Lannie; Ahmad, Zakiah (International Journal of Engineering and Technology, 2018)
This paper addresses the quality of the interface bonded joints in layers of timber elements. The shear performance was studied to assess the suitability of adhesive to bond timber with different thickness of glueline and timber densities. Since there is absolute test method in establishingÂ the shear strength of the surface bonds between layers timber elements, two test methods were used namely Thick Adherend Shear Test [TAST] and Lap Shear Test. The adhesived used is Sikadur-30 and timber used are Sesendok, Bintangor and Kempas with average densities 400-600kg/m3, 600-800kg/m3 and 800-1000kg/m3 respectively. Obtained results suggest that the interface stress distribution are related to the thicknesses of adhesive and densities of timber.Â Â